SIMBOLISME DAN MAKNA TEOLOGIS SUDHI WADANI DALAM KERANGKA FILSAFAT HINDU - Jelantik, Sayu Kadek (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
This study aims to examine the symbolism and theological meaning contained in the structure of the Sudhi Wadani ceremony through a Hindu philosophical approach, particularly those derived from the Vedas, Upanishads, and tattwa teachings. The research method uses a qualitative approach with observation techniques, in-depth interviews, and document studies with religious practitioners, traditional leaders, and relevant religious texts. The results of the study show that each stage of the Sudhi Wadani ceremony, from physical and spiritual cleansing, chanting mantras, offering banten, to the declaration of dharma, contains symbolism that represents the process of self-purification, transformation of consciousness, and reaffirmation of the relationship between Atman and Brahman. The theological meaning of Sudhi Wadani is oriented towards personal purification and the affirmation of life ethics through Tri Kaya Parisudha and the realization of the concept of moksha as the ultimate goal of humankind. Sudhi Wadani is not merely a ceremonial ritual, but a practice of Hindu philosophy of life that emphasizes the transformation of consciousness towards spiritual purity. The symbolism present in this ritual depicts the process of humankind's return to its true self (Atman), while its theological meaning emphasizes the cosmic connection between humans, nature, and Brahman. Thus, Sudhi Wadani has strong relevance as a spiritual practice that unites aspects of ritual, theology, and philosophy into a unified whole.